1998
DOI: 10.1111/j.1834-7819.1998.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal epithelial hyperplasia in an HIV positive man. An illustrated case and review of the literature.

Abstract: Focal epithelial hyperplasia (FEH) is a rare but distinctive entity of viral aetiology with characteristic clinical and histopathological features. It is usually seen in children and adolescents of American Indian and Eskimo background; however, it has recently been described in adults who are HIV positive. Suppression of the immune system leaves the individual vulnerable to opportunistic infections. With improved management of immunocompromised patients it is increasingly possible that the general dental prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
1
20
0
5
Order By: Relevance
“…It is associated with human papilloma virus (HPV) infection – most commonly HPV types 13 (hpv13) and 32 – with which it shares characteristic clinical and histopathological features [1, 2]. The development of FEH seems to be affected by several factors, such as genetic predisposition, local epithelial factors, the type of HPV and the immune status of the host.…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with human papilloma virus (HPV) infection – most commonly HPV types 13 (hpv13) and 32 – with which it shares characteristic clinical and histopathological features [1, 2]. The development of FEH seems to be affected by several factors, such as genetic predisposition, local epithelial factors, the type of HPV and the immune status of the host.…”
Section: Introductionmentioning
confidence: 99%
“…FEH is rarely associated with detectable immune suppression. However, increased incidence of FEH in HIVpositive patients has been observed [18,29,30]. It is suggested that the immunodeficiency in HIV infection increases the risk of the HPV-related FEH and its subsequent recurrences, but the relationship needs further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of epithelial hyperplasia varies, including basal epithelial battle-axe-shaped projections that occasionally anastomose horizontally, koilocytes (characterized by a clear cytoplasm and absent nucleus) and other intracellular changes characteristic of viral infections such as hyperchromatism and enlargement of nuclei [17]. The degenerating epithelial cells' nuclei resemble various phases of mitosis and are called mitosoid figures [12,18]. These are mostly found in the upper part of the epithelium and in lesions which are not fully developed but are not consistently present.…”
mentioning
confidence: 99%
“…Assim, relacionando a presença dessa doença a certos grupos étnicos, podemos afirmar que é provável existir um co-fator genético (15) . Também sabemos da relação de subtipos do HPV 13 e/ou 32 com essa doença, o que pode ser demonstrado por estudos imuno-histoquímicos e, mais recentemente, utilizando hibridização in situ (9) . As lesões descritas foram observadas na mucosa oral da paciente, que foi encaminhada para avaliação médica, mas não foram constatadas lesões na vagina ou na região anal.…”
Section: Figura 2 -Nódulos De Superfície Lisa Na Mucosa Interna Do Láunclassified
“…Poucos casos foram reportados fora das Américas, sendo relatados um no Japão, parcos Num estudo realizado constatou-se a necessidade de cortes seriados para se identificar as células mitosóides, pois as mesmas podem não estar presentes em um único corte (4) . Estudos recentes têm indicado a presença de hiperplasia epitelial focal em pacientes infectados pelo HIV (7,9,13) .…”
Section: Figura 2 -Nódulos De Superfície Lisa Na Mucosa Interna Do Láunclassified